F. A. Hayek's family and the Vienna circles - Bruce Caldwell; Hansjörg Klausinger (Duke University, Center for the History of Political Economy (CHOPE), 2021)
This working paper - like its companion, Caldwell and Klausinger 2021 - grew out of the authors' joint work on Hayek: A Life 1899-1950 (Caldwell and Klausinger 2022) and it contains material supplementing it. This paper examines the intellectual circles of fin-desiécle Vienna in which the Hayek family moved and which therefore shaped Fritz's education. After looking at the academics within the Hayek family we turn towards the intellectual communities in which Friedrich's father, August von Hayek, participated. Here we focus on the various associations of biologists and botanists and on the so-called "Brunnwinkl community." We show that participation in these circles resulted in Fritz coming in close contact with future Nobel prize winners like Erwin Schrödinger, Karl von Frisch and Konrad Lorenz. Austrian School economists Eugen von Böhm-Bawerk and Friedrich von Wieser were also among the close friends of the Hayek family. Finally, we point out a link to Austria's early liberal women's movement.
Keywords: 330; Friedrich Hayek; Juraschek; Wieser; Böhm-Bawerk; Schrödinger; Exner; Vienna; Brunnwinkl; liberalism; Austrian women's movement